Konsumsi Jenis Sayur Tinggi Kalium Berhubungan Dengan Tingkat Hipertensi Pada Lansia Di Puskesmas Dau - Buma, Iga Setiana; Putri, Rona Sari Mahaji; Devi, Hilda Mazarina (Universitas Muhammadiyah Lamongan, 2025)
Introduction: Hypertension in the elderly is one of the growing global health problems. One of the influencing factors is the low consumption of vegetables high in potassium. This study aims to determine the relationship between consumption of high potassium vegetable types and the level of hypertension in the elderly. Methods: This study used a cross sectional design. Participants consisted of 44 elderly people with hypertension who were selected by accidental sampling technique from the elderly population who routinely conduct health checks at the first level health service facility. Inclusion criteria are elderly who have been diagnosed with hypertension and are willing to become respondents, while exclusion is elderly with communication disorders. The instrument used was a modified Food Frequency Questionnaire (FFQ), while a tensimeter was used to measure blood pressure. Data analysis was performed using the Spearman rho test. Results: Most respondents (65.9%) had high potassium vegetable consumption in the sufficient category. The majority of elderly people experienced prehypertension and stage 1 hypertension, each as much as 43.1%. The results of the analysis showed that there was a significant relationship between consumption of high potassium vegetable types and the level of hypertension in the elderly (p-value = 0.000; r = -0.253). Conclusion: Elderly people who have adequate vegetable consumption are associated with blood pressure problems. This study suggests the need for further research on the amount and portion of vegetable consumption and the use of more accurate food recording methods.